Artabotrys brachypetalus Benth.: Evaluation of its traditional uses, phytochemistry, and pharmacological properties - Alfred Maroyi (Journal of Medicinal Plants for Economic Development, 2024)
Background: Artabotrys brachypetalus is best known for its edible fruits, but today, it is a well-known medicinal plant. However, there are several uses of the species, some of them known since prehistoric times.